Psychological jurisprudence as an interdisciplinary science and the area of psychological practice - Pozdnyakov, V.M. (Psihologiâ i pravo, 2017)
The article convincingly demonstrates that Russia is increasingly began to publish monographs lawyers on key legal and psychological phenomena, and in dissertations in the formulation of the provisions on the protection of delatsya criticism of "Westernization" of the state legislation and upheld psychologicaland position. At the same time, critically, it is noted that in the field of legal ideology and policies, and in making innovations in the law still, as in Soviet period, dominated by legal dogma, and psychological realities are taken into account in fragments. The reason for this state of Affairs is that still within the framework of University training and further education of local lawyers, in contrast to international practice, insufficient attention is paid to the development of psychological culture, but in the end no full-fledged dialogue between lawyers and psychologists. Taking into account possibilities of integrative methodology justified the subject of psychological law as an interdisciplinary science and the field of psychological practice focused on the identification of regularities and mechanisms of development of legal awareness and legal existence of various actors in the legal activity aimed at the development of psychologically informed interventions for the improvement of legal ideology and politics, systems of law-making, law enforcement and crime prevention, psycho-technical methods and techniques in activities of law enforcement officials. For constructive development of psychological jurisprudence identified the key areas of research and nodal practicerelevant problems. В статье аргументировано показано, что в России все чаще стали издаваться монографии юристов по ключевым юридико-психологическим явлениям, а в диссертациях при формулировании положений на защиту делатся критика по «вестернизации» отечественного законодательства и отстаиваются психологизированные позиции. В то же время критически отмечается, что в области правовой идеологии и политики, а также при внесении инноваций в законодательство по-прежнему, как и в советский период, доминирует правовая догматика, а психологические реалии учитываются фрагментарно. Причина подобного положения дел в том, что до сих пор в рамках вузовской подготовки и дополнительного образования отечественных юристов, в отличие от зарубежной практики, недостаточное внимание уделяется развитию психологической культуры, а в итоге нет полноценного диалога между юристами и психологами. С учетом возможностей интегративной методологии обоснован предмет психологической юриспруденции как междисциплинарной науки и области психопрактики, ориентированной на выявление закономерностей и механизмов развития правосознания и правового бытия различных субъектов правовой активности и направленной на разработку психологически обоснованных мер по совершенствованию правовой идеологии и политики, систем правотворчества, правоохраны и профилактики правонарушений, психотехнических методов и приемов в деятельности сотрудников правоприменительных органов. Для конструктивного развития психологической юриспруденции обозначены ключевые направления научных исследований и узловые практикориентированные проблемы.